Fashion and psychoanalysis : styling the self - Bancroft, Alison (International library of cultural studies, 2012)
"In this innovative new book, Alison Bancroft re-examines significant moments in twentieth century fashion history through the focal lens of psychoanalytic theory. Her discussion centres on studies of fashion photography, haute couture, queer dressing, and fashion/art in an attempt to shed new light on these key issues. According to Bancroft, problems of subjectivity are played out through fashion, in the public arena, and not just in the dark, unknowable unconscious mind. The question of what can be said, and what can only be experienced, and how these two issues may be reconciled, become questions that fashion addresses on an almost daily basis. By interpreting fashion within a psychoanalytic frame, Bancroft illustrates how fashion articulates some of the essential, and sometimes frightening, truths about the body, femininity and the self."